SENSITIVITY PATTERN OF E. COLI ISOLATED FROM CLOACA OF LAYING HENS WITH DIARRHEA AGAINTS STREPTOMISIN, KANAMISIN AND DOKSISIKLIN - Dwipayana, I Made Adhi Kusuma; Gelgel, Ketut Tono Pasek; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2022)
The aim of this study was to determine the sensitivity of E. coli bacteria isolated from cloacal swabs of laying hens with diarrhea to streptomycin, kanamycin and doxycycline. A total of 16 samples were used from farms in the villages of Utu (Tabanan), Perean (Tabanan), Demulih (Bangli) and Pasedahan (Karangasem). The sensitivity test of E. coli bacteria used the disc diffusion method from Kirby Bauer. Data analysis was carried out descriptively with the cross tabulation method. The results of 16 isolates of E. coli which were divided into 4 age groups isolated from laying hens cloacal swabs showed a pattern of sensitivity to streptomycin 62.5%  resistant, 18.75% intermediates and 18.75% sensitive. The pattern of sensitivity to kanamycin showed an intermediate 6.25% and the sensitivity result was 93.75%. To doxycycline resistance 50%, intermediate 18.75% and sensitive 31.25%. There is an increase in E coli resistance to streptomycin at >4 months of age, while doxycycline at 2-4 months of age and increasing at >4 months of age.